PERLINDUNGAN HUKUM ATAS HAK-HAK TERSANGKA PADA PROSES PENYIDIKAN PERKARA PIDANA DALAM PERSPEKTIF HAK ASASI MANUSIA - Dinanti, Dinda; Wahyuningsih, Yuliana Yuli (Jurnal Yuridis, 2016)
The only rules to be the basis for the implementation of the criminal procedural law is the Law of the Republic of Indonesia No. 8 of 1981, the ice shelf (for eign) No. 3209 of the Law Criminal Procedure law enacted on December 31, 1981, often called the Book of the Law of Criminal Procedure Law. In the article-article it reflected the protection of Human Rights (Human Rights). Detention is often done without regard to the terms of subjective and objective requirements as contained in the Code of Criminal Procedure. Arbitrary action by the investigator an conducting forceful measures. This study uses the research literature and then described in the findings and analysis. Law in Indonesia has guaranteed rights of the accused in various laws and regulatons in force in Indonesia, including UUD 1945, Universal Declaration of Human Rights, ICCPR, CAT and others. And one of the principles that embraced known as ?the presumption of innocence?, which is no one maybe arrested, detained and was arbitrarily be considered guilty of committing before he was convicted by the Court through a decision which has legal force (in kracht van gewisjde).